Peningkatan Pendapatan Pengrajin melalui Produksi Briket Ramah Lingkungan - Sukamta Sukamta; Indardi Indardi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The problems faced by coconut shell charcoal craftsmen are production capacity, product quality, and low selling prices. Low product quality is due to the absence of quality standards in the production process. This activity aims to improve the management quality and add value to charcoal products by turning them into briquettes to increase the selling price. Implementing activities is divided into two different problem areas that one partner handles: production problems and management problems (raw material management, production process management, packing, and warehousing management, shipping management, product quality assurance management, and marketing management). The output of this community service activity is that coconut shell charcoal has been produced with an increased quality than before in terms of the low water content of less than 7%. Likewise, the briquettes to those produced are of high quality. There is an increase in added value through processing shell charcoal into briquettes which have significantly increased revenue and profit.